Legal Implications on the Status of Individual Companies of Shares Inheritable to Foreign Heirs - Safitri, Nanda Melinia; Santoso, Budi; Syafi'i, R. Imam Rahmat (IJBLE Scientific Publications Community Inc., 2024)
If a shareholder of an individual company who dies in a mixed marriage, then their shares will transfer to foreign entities. This situation can cause confusion regarding the company's status. Therefore, this research will examine and analyze the legal consequences that inheriting shares from foreign heirs can have on the company's status. This writing uses a type of normative juridical research supported by an argumentum per analogy approach. The results of the research show that the legal consequences of inheriting shares from foreign heirs is that the obligation to change the company’s status to a capital partnership company by changing the list of shareholders and adding capital to the company. If the heirs do not wish this change, they can transfer their shares either by gift, exchange, or selling. Can also make a deed of transfer of inheritance rights to the shares to one heir who is an Indonesian citizen.